(untitled) (Revista Internacional de Folkcomunicação, 2020)
This research aims to present the academic studies that were carried out based on the theory of folkcommunication with a focus on folkmarketing, which is an organizational communication strategy, in the period from 2009 to 2018 (10 years). The state of the art provides support and proves the feasibility of a research. It also proves that the study contributes to the field of performance of Folkcommunication and Folkmarketing, as theories of communication. It has relevance for the academic area, because, despite being genuinely Brazilian, their use is still scarce and needs to be propagated in the field of research, especially in communication, due to its social relevance (studies that prioritize minorities that are on the margins of society). We conclude that bibliometric studies are invaluable tools for the area of ​​information science, as they apply statistical and mathematical methods in order to analyze and build indicators on the dynamics and evolution of scientific and technological information, quantifying the processes of written communication, for journals and for the development of science as a whole. Folkcommunication; Folkmarketing; Marketing Communication; Popular culture; Parintins.